Recent Development of Hydrogen Sulfide Releasing/Stimulating Reagents and Their Potential Applications in Cancer and Glycometabolic Disorders - Yang, Chun-tao; Chen, Li; Xu, Shi; Day, Jacob J.; Li, Xiang; Xian, Ming (Frontiers in Pharmacology, 2017)
As an important endogenous gaseous signaling molecule, hydrogen sulfide (H2S) exerts various effects in the body. A variety of pathological changes, such as cancer, glycometabolic disorders, and diabetes, are associated with altered endogenous levels of H2S, especially decreased. Therefore, the supplement of H2S is of great significance for the treatment of diseases containing the above pathological changes. At present, many efforts have been made to increase the in vivo levels of H2S by administration of gaseous H2S, simple inorganic sulfide salts, sophisticated synthetic slow-releasing controllable H2S donors or materials, and using H2S stimulating agents. In this article, we reviewed the recent development of H2S releasing/stimulating reagents and their potential applications in two common pathological processes including cancer and glycometabolic disorders.